Health economics and healthcare reform : breakthroughs in research and practice (Medical Information Science Reference, 2018)
"This book is a comprehensive source of academic material on the importance of economic structures and policy reform initiatives in modern healthcare systems. Highlighting a range of pertinent topics such as clinical costing, patient engagement, and e-health" -- Resumé vydavatele
Keywords: ekonomika zdravotnictví; reforma zdravotnictví; zdravotní péče; medical economics; health care reform; health care; sborníky; elektronické knihy; papers of several authors; electronic books